Van der Waals Heterostructures: Temperature‐Dependent Electronic Ground‐State Charge Transfer in van der Waals Heterostructures (Adv. Mater. 29/2021). Issue 29 (20th July 2021) - Park, Soohyung; Wang, Haiyuan; Schultz, Thorsten; Shin, Dongguen; Ovsyannikov, Ruslan; Zacharias, Marios; Maksimov, Dmitrii; Meissner, Matthias; Hasegawa, Yuri; Yamaguchi, Takuma; Kera, Satoshi; Aljarb, Areej; et al.
Abstract : The amount of charge transfer between components of a van der Waals heterostructure to reach the electronic ground state can exhibit a strong temperature dependence. In article number 2008677, Mariana Rossi, Norbert Koch, and co‐workers experimentally observe that the amount of ground‐state charge transfer in a van der Waals heterostructure formed by monolayer MoS2 sandwiched between graphite and a molecular electron‐acceptor layer increases by a factor of 3 when going from 7 K to room temperature.